Plagiat jako immanentna granica wolności twórczości artystycznej: [“Plagiarism as an immanent limit of artistic freedom“ presents the main problems of copyrights relation to the contemporary arts] (Studia Prawnicze / The Legal Studies, 2011)
Platońska teoria mimesis przez długi czas wyznaczała paradygmat myślenia o funkcji sztuki, za którą uważano odwzorowywanie otaczającego świata. Stosunkowo wcześnie jednak, bo już w czasach starożytnego Rzymu „sztuka zaczęła naśladować samą siebie”, a dzieła mistrzowskie admirowano przez sporządzanie ich kopii. Naśladowanie starożytności w sztukach plastycznych, charakterystyczne dla renesansu, utwierdzone zostało w drugiej połowie XVII wieku przez system akademickiej edukacji, wedle którego podstawą kształcenia było kopiowanie dzieł dawnych mistrzów (twórców renesansowych), stosowane przez nich sposoby obrazowania traktowano bowiem jako najlepsze z możliwych rozwiązań problemów artystycznych.  The beginning of this publication gives a brief explanation of the problem of appropriating the works of others and legal implication connected with it. This part seeks to explain the importance of the tendency in the contemporary visual arts to copy and appropriate the result of someone’s else creativity, first and foremost famous and easily recognisable works. As a rule the person, who created a specific work, owns the copyright of it. The creator is often called the author of the work. As practice shows this situation is often not that simple, especially in case with the appropriation. The second part of this article characterises the legal institution of plagiarism and the conditions of the copyrights’ protection. This chapter gives an answer of what the plagiarism is. Plagiarism is regulated by the art. 115 of the polish copyright law. The main part of the publication provides basic information about copyrights and related rights in the context of this regulation. This part answers the following questions: (1.) which special rules of plagiarism are relevant in case with folk art?, (2.) what is the relation between plagiarism and several forms of legal use such as quotation, inspired work and derrivated work? This part deals in particular with the challenges concerning the protection of copyrighted works in contemporary art. Here the answer to the question ‘what are the reasons of work’s similarities?’ is given. The next section is dedicated to show how the authors can find and use works in the public domain as well as what the public domain is. Copyright laws try to find a balance between the rights they give to authors and the right of the public to access and use these works. The creators also benefit from having an access and a possibility to use the works of previous authors, which inspire them and help them learn techniques, which can be used to develop new works. The public domain and copyright limitations provide this balance between the rights of authors and the rights of the public. It is important that different authors to create new works often use the works in the public domain. When an original work is translated, adapted or changed in any other form, the new work is called a derivative work. Derivative works are also protected by copyrights, even if the original works from which they were derived are in the public domain. The person who created the derivative work is its author and owns its copyright. If someone wishes to use (reproduce, translate, adapt, etc.) a derivative work, which is protected by copyrights, must obtain permission from the author. One of the important question of this section is: what happens in case with an anonymous work of art? One should take into consideration, that in some cases authors wish to remain anonymous or use a pseudonym in order to hide their true identity from the public. In these cases, the author still owns the copyright to his works. The final part of the publication explains three common types of copyright infringement and how they can be avoided. Infringement takes place when a copyrighted work is used (reproduced, translated, adapted, exhibited or performed in public, distributed, broadcasted, or communicated to the public) without the permission of the right holders or under a limitation to copyright. The main copyrights infringement is plagiarism, which means the act of copying a work, wholly or partially, and then pretending to be its original author. In conclusion some additional information is given, which includes the most important questions about the use of copyrights in the practice.